Hydroponic: Empowering Local Farmer Knowhow to Gain Value Added on Agriculture Commodity - Suryaningprang, Andre; Suteja, Jaja; Mulyaningrum, Mulyaningrum; Herlinawati, Erna (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The agricultural sector is one of the potential commodities in business at domestic and abroad, local farmers in the West Java area are trying to run the best farming system that is adapted to market needs. Conventional farming systems that require large tracts of land, the availability of farmer labor and the length of time for harvesting are obstacles for local farmers to expand their businesses and increase their production yields. A concept in the agricultural system that is different from conventional agriculture yet can be used by local farmers at this time is hydroponic farming. Hydroponic farming that uses water as a planting medium can be implemented anywhere such as urban areas because it does not require large tracts of land. One of the hydroponic techniques that is currently developing is the NFT or Nutrient Film Technique which can be applied in the highlands and lowlands. This system can provide quality harvests. The NFT system provides added value for farmers by increasing farmers' knowledge about the hydroponic farming system and increasing agricultural commodities produced, through this system the farmers can run their farming business on land that is not extensive in urban areas. The commodities produced are of high quality because they are environmentally friendly, with efficient fertilizer, water and the use of non-pesticide ingredients. In fact, this hydroponic system requires a large enough cost to purchase material, regardless of the greater quantity of harvest and shorter harvest time. Increasing the quality and quantity of agricultural products encourage local farmers to run a hydroponic system in meeting market needs so that they have high economic value and can improve the welfare of local farmers.